RESEARCH ON THE APPLICATION OF MODERN APPRENTICESHIP SYSTEM IN HIGHER VOCATIONAL TRANSPORTATION SPECIALTY FROM THE PERSPECTIVE OF EMOTION REGULATION - Jiang, Bolin; Ji, Min; Wu, Shanshan; Song, Ying (The international journal of neuropsychopharmacology, 2022)
Abstract Background With the support and advocacy of the state, China's higher vocational education has actively tried and tried out the modern apprenticeship model. However, due to the late start of theoretical research, weak foundation and lack of practical experience, the development effect of modern apprenticeship is not ideal. For individual majors in higher vocational colleges, such as transportation, there is less applied research on educational psychology. Therefore, in the context of emotion regulation, it is very important to study the application of modern apprenticeship in Higher Vocational transportation specialty. Subjects and Methods In view of this, this paper selects higher vocational colleges, enterprises and students for online questionnaire survey from the perspective of educational psychology. The research objects include 25 National Demonstration Higher Vocational Colleges and provincial demonstration transportation higher vocational colleges; 22 enterprises are engaged in bridge and tunnel, road maintenance, traffic operation management, intelligent transportation and other industries, and have experience in school enterprise cooperation; 58 modern apprenticeship graduates. With the theme of “modern apprenticeship transportation talent training in Higher Vocational Colleges”, the questionnaire is designed around the hot issues in the development of modern apprenticeship, such as school enterprise cooperation, teaching staff, student management, employment welfare and so on. Better investigate the emotional changes of apprentices under the professional background. The study also used the auxiliary scale related to emotion, self rating Anxiety Scale (SAS), which was compiled by Zung in 1971. From the form of scale construction to the specific evaluation method, it is very similar to the self rating Depression Scale (SDS). It is also a self-evaluation scale with 20 items and four grades, which is used to evaluate the subjective feelings of the visitors. SAS is a very simple clinical tool for analyzing patients' subjective symptoms. 36 patients with neurosis were assessed by SAS and examined by HAMA scale. The correlation coefficient of Pearson correlation method and Spearman grade correlation coefficient of the total scores of the two tables were 0.36 and 0.341 respectively. The results showed that the validity of SAS was quite high. Foreign studies believe that SAS can accurately reflect the subjective feelings of psychiatric patients with anxiety tendency. Anxiety is a common emotional disorder in psychological counseling clinics. In recent years, SAS has been used as a self-assessment tool to understand anxiety symptoms in counseling clinics. Before the self-assessment, ask the self assessor to understand the filling method of the whole scale and the meaning of each question, and then make an independent self-assessment that is not affected by anyone. Before starting the assessment, the staff pointed to the SAS scale and told him: there are 20 words below. Please read each one carefully to understand the meaning, and then tick (√) in the appropriate box according to your actual situation in the last week. There are four squares after each text. Respectively represents no or little (occurrence), a small part of time, a considerable amount of time, most or all of the time. If the assessor's education level is too low to understand or understand the SAS problem content, the staff can read it to him, read it item by item, and let the assessor make the assessment independently. One assessment can generally be completed within ten minutes. Results Through the analysis of the survey results, it can be seen that higher vocational colleges and teachers have a high enthusiasm to participate in the implementation of modern apprenticeship, the training mode of modern apprenticeship is basically formed, and the training objectives are clear. Developing modern apprenticeship system can improve students' comprehensive professional quality and is of great help to students' employment and future development. Modern apprenticeship system can also meet the needs of talent training and bring certain benefits to enterprises. However, in the process of implementation, there are still some urgent problems to be solved, such as the lack of guarantee of teaching management and operation mechanism, the signing of contracts between enterprises and students, the weak professional foundation of students, weak work and so on. Environment, etc. In view of the above problems, this paper puts forward some implementation strategies. For example, introduce “double qualified” teachers and pay attention to the cultivation of practical skills. Clarify the employment prospects of students and analyze the current employment situation. Formulate scientific apprentice assessment standards and flexible assessment mechanism. Attract government funds and strengthen school enterprise cooperation. Through the test of the anxiety level of students with employment prospects, the average total score of SAS is 42.98 ± 9.94. Among them, the score was 40.52 ± 6.62, and the score of 48 anxious students was 45.68 ± 11.23. The result of f-value test was not significant, P > 0.05. It shows that SAS can not distinguish the severity and particularity of anxiety, and other self-rated anxiety scales must be applied at the same time. For other norm research results, the average value of 15 single scores of positive evaluation questions is 1.29 ± 0.98; The average score of the five reverse items is 2.08 ± 1.71, and the average value of the total score of 20 items is 29.78 ± 0.46, which can be used as the upper limit of the average value of the total score of the norm. Students with high employment prospects have a downward trend in anxiety level. Conclusions This paper studies the application of modern apprenticeship in Higher Vocational transportation specialty from the perspective of educational psychology. The results show that the implementation of modern apprenticeship talent training mode in China has promoted the reform of education and teaching and the transformation and upgrading of transportation, and can effectively promote the development of education. Acknowledgements This research was supported by Chongqing Municipal Education Commission Higher Education Teaching Reform Research Project (Research and Practice of International Talent Training Mode under the Background of “The Belt and Road Initiative”), Education and Teaching Reform Research Project of Chongqing Vocational Institute of Engineering (Grant No. JG221011).